Obtenção de aplicativo para uso na predição de risco hipertensivo e nível de atividade física em adolescentes - SOARES JUNIOR, Nivaldo de Jesus Silva (2023)
Introduction: Chronic non-communicable diseases are causes of 7 out of 10 deaths annually worldwide, where about 80% of this mortality occurs in developing countries such as Brazil. Among these diseases, we have Arterial Hypertension (AH). One of the causes of this disease is physical inactivity itself, which has also been rising to alarming levels and this behavior begins since childhood and adolescence, including a greater use of technologies that has moved away from a healthy practice, but it should be used in favor of an active lifestyle. In addition, the Family History of Hypertension (FHH) and genetic polymorphism as an important predictor in its prevalence, in which the response already presents itself from the very early age in the autonomic nervous system (ANS) of these individuals, as an aggravating factor. Objective: develop a software for the evaluation of autonomic dysfunction and hypertensive risk in adolescents with different levels of physical activity and genetic polymorphism. Methods: This analytical and cross-sectional study included 288 adolescents between 11 and 18 years of age from a public school in São Luís - MA. The sample was divided by the family history of arterial hypertension and later by the level of physical activity. Subsequently, it was classified according to the polymorphism of the ACE gene (DD, DI, and II), where the characterization parameters were evaluated: age, weight, height, BMI, WC, Tanner, and PSQI; hemodynamic parameters: SBP, DBP, and HR; autonomic parameters: through electrocardiogram and analysis of heart rate variability in the time and frequency domain; genetic parameters: saliva collection and DNA extraction through PCR; and programming of a software that makes use of genetic and autonomic variables in the indication of the adolescent’s physical activity. All research was built over four articles to reach the final result. Results: it was observed that the sample was homogeneous regarding sexual maturation. In the initial characterization, we saw a vagal reduction in the offspring of hypertensive parents and an increase in SBP in all genotypes. However, compared to the offspring of normotensive with the genotypes DI and II. In addition, when dividing by the level of physical activity, the differences showed a higher BMI in sedentary patients and minor HR in those who were active. Finally, when analyzing the autonomic variables, we observed a higher vagal activity in the active group in all genotypes but a higher magnitude in the active group of II genotype. With this data, a software was created using the Decision Tree algorithm to cross-reference the data and have a good accuracy. Conclusion: we can conclude the influence that the family history of arterial hypertension has on the autonomic modulation of adolescents, as well as the ACE gene polymorphism; and the importance of the regular practice of physical activity in improving this vagal activity reduction that affects offspring of hypertensive parents and in reducing ACE activity in individuals who have the D allele, as a possible protective factor in the involvement of arterial hypertension in this population. Therefore, we conclude with the creation of the software that uses through these parameters used in the study to obtain the best recommendation of physical activity for adolescents..